Catcalling In Syari’at: Islamic Perspective And Challenges In Aceh - Baharuddin, Hasan Sazali, Elfi Yanti Ritonga, Zulfadli (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to analyze the occurrence of events catcalling in public space based on Islamic Sharia measurements. These measurements are considered part of the process communication between communicator and communicators regarding the handling of the catcalling phenomenon that often occurs in public space, which then became a challenge for the Acehnese people . The type of research is descriptive research using a qualitative approach, with in-depth interview techniques. The results of the study showed that the causes the occurrence catcalling explains that, first, the role of Islamic Sharia institutions related to catcalling is still being carried out in a marathon. However, one thing that should be underlined is that catcalling events have given rise to a negative stigma where such behavior is seen as an immoral act and does not reflect the dignified side of human behavior. This means that all victims of catcalling admit to experiencing prolonged trauma, difficulty speaking, low self-confidence, loss of thinking orientation and difficulty interacting with each other. Second, regarding legal certainty . This side is due to the stagnation in terms of the use of legal instruments between local products (qanun) or national products (Laws). Third, catcalling actions considered as a normal thing in society, so that this behavior is sometimes considered not a violation of the law. Therefore, in the author's opinion, Islamic communication principles are needed as an alternative instrument as a form of mitigation that prioritizes both the content of the message, the interaction between the communicator and the communicant, and or socio-cultural traditions that have developed into critical ones while still upholding the spirit of ethical values proportionally and with dignityy